Asymmetric synthesis of the marine alkaloid (-)-(S)-nakinadine C - Davies, S; Roberts, P; Shah, R; Thomson, J (2013)
The first asymmetric synthesis of the marine alkaloid (-)-(S)-nakinadine C is described. This synthesis employs the conjugate addition of lithium dibenzylamide to an N-α-phenylacryloyl SuperQuat derivative followed by diastereoselective protonation of the intermediate enolate using 2-pyridone as the key step to introduce the stereochemistry. (-)-(S)-Nakinadine C was isolated in 13% yield over 9 steps from commercially available atropic acid, 98:2 dr [(Z):(E) ratio] and >99% ee. © 2013 Elsevier Ltd. All rights reserved.